Application of Modified Flax Fibres as Bio-Sorbents for the Removal of Ammonia from Liquid Phase - Wylie, Declan Alexander (Université d'Ottawa / University of Ottawa, 2025)
Ammonia is among the most released pollutants into Canadian waters. It is generated from a wide range of sources, including mining and agriculture, among others. The consequences resulting from high concentrations of ammonia include depletion of dissolved oxygen, lake eutrophication, and toxicity to aquatic animals. Several methods exist for the treatment of ammonia in wastewater streams, though many employ synthetic, non-sustainable materials. In turn, these create their own waste stream and can be economically unviable. As a result, interest in developing sustainable and cost-effective methods continues to be an area of research in the scope of water treatment. Biosorbents (adsorbent materials derived from organic matter) are an area of particular focus due to the sustainable and low-cost nature of these materials. Further benefits include their capacity to be modified via chemical treatments and oxidation to improve surface characteristics. In this study, flax fibres were evaluated for their feasibility for the removal of ammonia from aqueous solution. This was achieved by conducting batch testing at various phases in the treatment and oxidation process. The goal of these tests was to establish any improvement in ammonia removal between the fibres as they were received and the fibres after undergoing treatment and oxidation. Fully treated fibres were found to have produced the largest maximum uptake capacity, based on the Langmuir model, at a value of 3.373 mg/g, a noticeable improvement when compared to the fibres as received, which achieved a maximum uptake capacity of 0.912 mg/g. The effects of varying pH and temperature on the fibres' removal capacity was also studied. The pH value that produced the most efficient removal was in the range of 6-7. The reactions occurring during removal were found to be endothermic, and indications were that the removal reaction was kinetically favorable. Additionally, thermodynamic analysis showed that favourability was increasing with increasing temperatures. Furthermore, regeneration tests were conducted for three loading and unloading cycles. A comparison of the three different regeneration solutions used indicated that 5% and 10% NaCl solutions were more effective at maintaining the fibres' uptake capacity when compared to deionized water, though results showed there was no statistical difference in the effectiveness of the 10% solution when compared to the 5% solution. In all cases, however, fibre removal capacity was declining throughout the regeneration phases. The final phase of this study involved the characterization of the fibres' surfaces before and after treatment or testing via scanning electron microscopy (SEM), x-ray photon spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR) analysis. SEM imaging gave a visual analysis of the differences between fibres after various treatment stages. Results showed the removal of extractives, like lignin and hemicellulose from the fibre surface, as visual indicators of these extractives were not found in the SEM images of the treated and oxidized fibres. More detailed surface analyses using XPS and FTIR methods were helpful in confirming the removal of extractives and the presence of sodium carboxylate groups after oxidation. This further confirmed the earlier assumption that extractives had successfully been removed while also helping to determine that the oxidation procedure was a successful one.
Keywords: Ammonia; Flax fibres; Adsorption; TEMPO oxidation; Batch testing; Biosorbents; Uptake capacity; Surface characterization; Wastewater treatment